2008
DOI: 10.3324/haematol.12840
|View full text |Cite
|
Sign up to set email alerts
|

Significance of borderline hemoglobin A2 values in an Italian population with a high prevalence of  -thalassemia

Abstract: We report a retrospective analysis carried out on 23,485 subjects submitted to a screening program from 2000 to 2006. Of these subjects, 3,934 had borderline HbA2 values from 3.1 to 3.9%; 410 samples, analyzed previously using PCR methods and sequencing because all of these were partners of a carrier of classical ␤-thalassemia, were selected for statistical analysis. Of 410 subjects, 94 (22.9%) were positive for a molecular defect in the ␤-, ␦-or ␣-globin genes. The most prevalent molecular defects were ␤ IVS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 22 publications
3
42
1
Order By: Relevance
“…The false negative samples were 8 of 30 (26,6%): 3 presented Hb b variants, co-eluting with HbA, (Hb Valletta, Hb Ernz and Hb City of Hope) that do not require prenatal diagnosis, one showed an undefined single nucleotide polymorphism (SNP) in the b-globin gene of ambiguous diagnostic significance, 8 2 samples presented, respectively, the α-globin gene triplication (ααα anti3.7…”
mentioning
confidence: 99%
“…The false negative samples were 8 of 30 (26,6%): 3 presented Hb b variants, co-eluting with HbA, (Hb Valletta, Hb Ernz and Hb City of Hope) that do not require prenatal diagnosis, one showed an undefined single nucleotide polymorphism (SNP) in the b-globin gene of ambiguous diagnostic significance, 8 2 samples presented, respectively, the α-globin gene triplication (ααα anti3.7…”
mentioning
confidence: 99%
“…We examined our sequence results for such a mutation, but IVS-II-654 C>T mutation was not present in the presented family. Giambona et al reported HBB:c.*+96T>C mutation in an Italian patient with a slightly elevated HbA 2 level [10]. Moreover, Boussiou et al observed the HBB:c.*+96T>C mutation in 7 Greek patients without any clinical symptoms [11].…”
Section: Resultsmentioning
confidence: 99%
“…Study done among borderline HbA2 samples in Italian populations showed that out of 95 positive samples, majority which was 25.3% showed mutation IVS 1 nt6 [11]. Study done among Chinese in Southern Asia showed that out of 165 samples of borderline HbA2 (3.3%-3.7%), 9.1% were positive for molecular defect in α-or β-globin gene.…”
Section: Discussionmentioning
confidence: 99%
“…Out of that, 410 samples were proceed with molecular test which showed that 22.9% were positive for molecular defect in β, α (or) δ-globin genes [11].…”
Section: Discussionmentioning
confidence: 99%